2014
DOI: 10.1007/s10103-014-1609-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methylene blue-mediated photodynamic therapy for treatment of basal cell carcinoma

Abstract: Photodynamic therapy (PDT) is regarded as a treatment option for basal cell carcinoma (BCC). The aim of this study is to investigate the efficacy of methylene blue (MB)-based PDT in patients suffering from nodular or ulcerative BCCs. This study is a prospective clinical trial with a 6-months follow-up. The study setting is at the Dermatology Clinic at NILES, Cairo University, Egypt. Seventeen patients complaining of nodular BCC (nBCC) and three patients complaining of ulcerative BCC (uBCC) were taken as sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Liposomal MB formulations 314,315,316 were used in a PDT study of 20 patients with nodular and ulcerative basal cell carcinoma showed 11 patients to have complete response with good cosmetic outcome and minimal side effects after six months. 317 Toluidine blue (31) is another phenothiazine PS used in PDT for a long time. 318,319,320 Formulation in liposomes followed by incorporation into carboxymethylcellulose hydrogels (sometimes called a transferosome approach) and in vivo studies on subcutaneous Ehrlich tumor showed an increase in overall survival of mice when compared to treatment with free toluidine blue.…”
Section: Phenothiazinesmentioning
confidence: 99%
“…Liposomal MB formulations 314,315,316 were used in a PDT study of 20 patients with nodular and ulcerative basal cell carcinoma showed 11 patients to have complete response with good cosmetic outcome and minimal side effects after six months. 317 Toluidine blue (31) is another phenothiazine PS used in PDT for a long time. 318,319,320 Formulation in liposomes followed by incorporation into carboxymethylcellulose hydrogels (sometimes called a transferosome approach) and in vivo studies on subcutaneous Ehrlich tumor showed an increase in overall survival of mice when compared to treatment with free toluidine blue.…”
Section: Phenothiazinesmentioning
confidence: 99%
“…The procedure was similar to that of our previous study [14]. The laser wavelength was 635 nm and the power was 280 to 300 mW.…”
Section: Case Presentationmentioning
confidence: 99%
“…The reported photosensitizers are mainly porphyrin-based derivatives ( Lucky et al, 2015 , Ormond and Freeman, 2013 ). Several classes of non-porphyrin derivatives, such as cyanines ( Fekrazad et al, 2015 , Gluth et al, 2015 ), xanthenes ( Gianotti et al, 2014 , Wang et al, 2013 , Yao et al, 2014 ), phenothiazines ( Samy et al, 2015 , Yu et al, 2015 ), and anthraquinones ( Sharma and Davids, 2012 , Theodossiou et al, 2009 ) were investigated recently. Most of the reported photosensitizers absorb light in the visible region.…”
Section: Introductionmentioning
confidence: 99%